Calorimetric and Thermal Analysis Studies on the Influence of Coal on Cement Paste Hydration - Noureddine. Bentaieb; Zine el Abidine Benarima; Salah Belaadi (Iranian Journal of Chemistry & Chemical Engineering, 2020)
Composite Portland Cement, CEMII (cement with additives of limestone, slag from blast furnaces, tuff, and pozzolan) represent a significant share of the cement manufacturing in the world. These additives can increase cement production and reduce the energy consumption in this sector, their incorporation in the milling process of the clinker allow also to obtain hydraulic blinders better homogenized and more responsive. Blended types of cement are grounded more finely than the pure cement between 3500 to 5000 cm2/g. The use of industrial waste, as well as natural products such as pozzolan and limestone as partial replacement of clinker in cement and concrete, saves energy[1.2.3], and it reduces emissions of greenhouse gas. This results in the production of concrete non-polluting and sustainable environmentally. Our work was based on the incorporation of coal as additives (CEMI)and study the effect of this addition during the hydration reaction of the cement paste of the studied samples, with a heating rate of 5°C/mn, the percentages of coal used were (10% ,20% ,30%). Previous studies showed that coal has the ability to increase the mechanical resistance of cement, this is due to the chemical composition of the coal (SiO2, Ca, Fe2O3, Mg, Na), which affects the grind ability of the cement and its reaction with water(hydration reaction). Thermal analysis allows us to evaluate the heat released by the studied cement during its hydration and to exploit the results by using various models. The degree of hydration, the rate constant, and activation energy are determined, this energy is global, as it relates to all phases of hydration reactionsof cement namely (C3S, C2S, C3A, and C4AF).